2006
DOI: 10.1007/s00335-005-0174-0
|View full text |Cite
|
Sign up to set email alerts
|

High resolution mapping of chromosomal regions controlling resistance to gastrointestinal nematode infections in an advanced intercross line of mice

Abstract: Fine mapping of quantitative trait loci (QTL) associated with resistance to the gastrointestinal parasite Heligmosomoides polygyrus was achieved on F(6)/F(7) offspring (1076 mice) from resistant (SWR) and susceptible (CBA) mouse strains by selective genotyping (top and bottom 20% selected on total worm count in week 6). Fecal egg counts were recorded at weeks 2, 4, and 6, and the average was also analyzed. Blood packed cell volume in weeks 3 and 6 and five immunological traits (mucosal mast cell protease 1, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 44 publications
4
36
2
Order By: Relevance
“…Interestingly, one chromosomal region identified by these researchers was the MHC located on mouse chromosome 17. Their observations were confirmed independently by Behnke et al [33] who found associations between eight immunological traits (FEC at weeks 2, 4, and 6, mucosal mast cell protease 1, granuloma score, IgG1 against L5, and IgG1, and IgE to L4) and QTLs on chromosome 1 and 17 associated with resistance to the H. polygyrus infection. More specifically, the MHC genes, most notably, the class II and TNF regions were significantly associated with gastrointestinal parasite infection.…”
Section: Genetic Factors In Gastrointestinal Parasite Immunitysupporting
confidence: 52%
“…Interestingly, one chromosomal region identified by these researchers was the MHC located on mouse chromosome 17. Their observations were confirmed independently by Behnke et al [33] who found associations between eight immunological traits (FEC at weeks 2, 4, and 6, mucosal mast cell protease 1, granuloma score, IgG1 against L5, and IgG1, and IgE to L4) and QTLs on chromosome 1 and 17 associated with resistance to the H. polygyrus infection. More specifically, the MHC genes, most notably, the class II and TNF regions were significantly associated with gastrointestinal parasite infection.…”
Section: Genetic Factors In Gastrointestinal Parasite Immunitysupporting
confidence: 52%
“…In addition to the evidence presented above they are also close to the peak of the QTL for FEC, adult worm specific IgG1 antibody (IgG-Ad) and packed cell volume in week 6 (PCV6), which is around 52 Mb (Behnke et al 2006a). However, it should be emphasized that the available evidence is not comprehensive at this stage and other genes could be responsible for or contribute to the observed differences in response.…”
Section: Discussionsupporting
confidence: 71%
“…This is the first experimental study to show unequivocally that the expulsion of H. bakeri worms from mice can be delayed by alleles of genes mapping in this region of mouse chromosome 1. Moreover, it is highly pertinent that this region maps well within the confidence intervals of the H. bakeri resistance QTL (Hbnr1) described in Behnke et al (2006a). Since the B10 insert is relatively short, it now allows our search for resistance genes to be focused on a few candidates within this region.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, expulsion and resistance to the small intestinal nematode Heligmosomoides bakeri in mice has been characterized at murine chromosome 1 and 17 [38] corresponding to Tm1 and Tm17 . Similarly, a study of Trichinella spiralis infection in rats, which causes acute and transient small bowel inflammation, identified a single significant QTL region homologous to the murine chromosome 1 locus ( Tm1 ) [39].…”
Section: Discussionmentioning
confidence: 99%